Job Demands and Performance Among Oil Palm Harvesters: Testing Work Stress Mediation - Mohammad Abiyyu Rendragraha; Endang Parahyanti (LPPM STIE KRAKATAU, 2026)
This study examined whether job demands predict job performance among oil palm harvesters and whether work stress mediates this relationship from the job demands–resources (JD-R) perspective. A cross-sectional correlational survey was conducted with 215 oil palm harvesters at PT X, Central Kalimantan. Data were analyzed using structural equation modeling (SEM) with the maximum likelihood (ML) estimator in JASP, including an indirect-effect test for mediation. Job demands did not significantly predict work stress (β= 0.072; p= 0.350), and the indirect effect through work stress was not significant (β= −0.016; p= 0.363). Job demands positively predicted job performance (β= 0.650; p< 0.001), whereas work stress negatively predicted job performance (β= −0.514; p< 0.001). In this plantation context, job demands appear to function more as performance-relevant (challenge-like) requirements rather than stress-inducing burdens, whereas work stress, when present, remains detrimental to performance. The study is limited by cross-sectional self-report data from a single firm and an all-male sample, and job resources were not measured. Nevertheless, it clarifies a non-mediated pathway and points to strengthening resources and stress management as targeted levers for sustaining performance.